PROJETO MARACANÃ - DO DISCURSO À PRÁTICA DA SUSTENTABILIDADE: Estudo sobre as percepções dos Agentes Ambientais e os reflexos do desenvolvimento das ações no meio ambiente, no lazer e na qualidade de vida. - Chaves, Janete Rodrigues de Vasconcelos (2007)
This work concerns about the relation among the environment, the leisure and the quality of life. It is a reflection about the Environmental Protection Area APA - of the Maracanã Region and its social and environmental situation. It aims to situate the theoretical issues and associate them to the practice when presenting the Maracanã Project and its major representatives: the Environmental Agents. It analyzes the Maracanã Project as a relevant and strategic proposal of leisure and tourism area in São Luís. It is a study of qualitative and quantitative approaches with data based on surveys. The results show up the realization of the process of professional formation of great value and social and economic importance which the Project has shown. It presents the formation of multiple people in natural areas is the way for its protection. It argues and confirms that this proposal deserves some highlight as an institutional and private support in the environmental and social improvement of the area to reach the sustainable development. It shows that the development of the leisure activities in natural environments is important to reach and keep a good quality of life because it is considered a social representation on the semantic field which it is developed the constructor quality of life on the subjective aspects of well-being, happiness, professional realization, friendship, personal realization and also objectives whose references are a satisfaction of basic needs created because of the degree of economic and social development the Maracanã community.